K-Ras prenylation as a potential anticancer target - Baranyi, Marcell (Cancer Metastasis Rev, 2020)
KRAS is one of the most commonly mutated oncogene and a negative predictive factor for a number of targeted therapies. Therefore, the development of targeting strategies against mutant KRAS is urgently needed. One potential strategy involves disruption of K-Ras membrane localization, which is necessary for its proper function. In this review, we summarize the current data about the importance of membrane-anchorage of K-Ras and provide a critical evaluation of this targeting paradigm focusing mainly on prenylation inhibition. Additionally, we performed a RAS mutation-specific analysis of prenylation-related drug sensitivity data from a publicly available database (https://depmap.org/repurposing/) of three classes of prenylation inhibitors: statins, N-bisphosphonates, and farnesyl-transferase inhibitors. We observed significant differences in sensitivity to N-bisphosphonates and farnesyl-transferase inhibitors depending on KRAS mutational status and tissue of origin. These observations emphasize the importance of factors affecting efficacy of prenylation inhibition, like distinct features of different KRAS mutations, tissue-specific mutational patterns, K-Ras turnover, and changes in regulation of prenylation process. Finally, we enlist the factors that might be responsible for the large discrepancy between the outcomes in preclinical and clinical studies including methodological pitfalls, the incomplete understanding of K-Ras protein turnover, and the variation of KRAS dependency in KRAS mutant tumors.